(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Physical deviations that are closely related to technological development helped to the emergence of diseases resulting from inactivity and lack of movement, So therapeutic exercise is one of the means to help improve the strength of pupils by using the means of assistance as a means of treating deviations of the spine such as (rubber ropes, medical balls, stick and various sponge pieces). The purpose of therapeutic exercises is to help the child return to activity and life as quickly as possible, reduce pain and increase the flexibility of joints and muscle elasticity. Therefore, the researcher used the one-group experimental curriculum (tribal after test), and the research community was identified from the 150 students and students of the 2018-2019 school year, and 22 students were identified. Their age of (6-9) years in the deliberate way, as the therapeutic program was implemented which includes therapeutic exercises for (6) weeks by (12) therapeutic units and the time of the therapeutic unit (35) minutes, and concluded the researcher that the therapeutic units followed by the researcher to reduce deviations in the column.